Hyperfast Water Transport through Biomimetic Nanochannels from Peptide‐Attached (pR)‐pillar[5]arene. Issue 6 (13th January 2019) - Li, Qing; Li, Xuesong; Ning, Lulu; Tan, Choon‐Hong; Mu, Yuguang; Wang, Rong
Abstract: Synthetic water channels offer great promise to replace natural aquaporins (AQPs) for making new‐generation biomimetic membranes for water treatment. However, the water permeability of the current synthetic water channels is still far below that of AQPs. Here, peptide‐attached (pR)‐pillar[5]arene (pR‐PH) channels are reported to mimic the high permeability of AQPs. It is demonstrated that the pR‐PH channels with an open pore can transport water smoothly and efficiently. The pR‐PH channels are competitive with AQPs in terms of water permeability and are much superior to diastereomer peptide‐attached (pS)‐pillar[5]arene (pS‐PH) and other reported synthetic water channels. The exceptional water‐transport properties of the pR‐PH channels are further demonstrated in a composite polymeric membrane that incorporates the nanochannels into the top selective layer. This membrane gives a significantly improved water flux while retaining high salt rejection. The results establish a tangible foundation for developing highly efficient artificial water channel‐based biomimetic membrane for water purification applications. Abstract : New‐generation synthetic water channels are created by introducing peptide‐attached pillar[5]arene with two diastereomers, peptide‐attached (pR)‐ and (pS)‐pillar[5]arenes, designated as pR‐PH and pS‐PH, respectively. The pR‐PH channels with open pore can allow water molecules to pass fast while pS‐PH channels are easily blocked by side chain and lose the permeation ability of water molecules.